B-Cell Reconstitution After Autologous Hematopoietic Stem Cell Transplantation in Multiple Sclerosis. Issue 6 (13th November 2022) - von Niederhäusern, Valentin; Ruder, Josefine; Ghraichy, Marie; Jelcic, Ilijas; Müller, Antonia Maria; Schanz, Urs; Martin, Roland; Trück, Johannes
Abstract : Background and Objectives: Autologous hematopoietic stem cell transplantation (aHSCT) is increasingly used to treat aggressive forms of multiple sclerosis (MS). This procedure is believed to result in an immune reset and restoration of a self-tolerant immune system. Immune reconstitution has been extensively studied for T cells, but only to a limited extent for B cells. As increasing evidence suggests an important role of B cells in MS pathogenesis, we sought here to better understand reconstitution and the extent of renewal of the B-cell system after aHSCT in MS. Methods: Using longitudinal multidimensional flow cytometry and immunoglobulin heavy chain (IgH) repertoire sequencing following aHSCT with BCNU + Etoposide + Ara-C + Melphalan anti-thymocyte globulin, we analyzed the B-cell compartment in a cohort of 20 patients with MS in defined intervals before and up to 1 year after aHSCT and compared these findings with data from healthy controls. Results: Total B-cell numbers recovered within 3 months and increased above normal levels 1 year after transplantation, successively shifting from a predominantly transitional to a naive immune phenotype. Memory subpopulations recovered slowly and remained below normal levels with reduced repertoire diversity 1 year after transplantation. Isotype subclass analysis revealed a proportional shift toward IgG1-expressing cells and a reduction in IgG2 cells. Mutation analysis of IgH sequences showed that highly mutated memory B cells and plasma cells may transiently survive conditioning while the analysis of sequence cluster overlap, variable (IGHV) and joining (IGHJ) gene usage and repertoire diversity suggested a renewal of the late posttransplant repertoire. In patients with early cytomegalovirus reactivation, reconstitution of naive and memory B cells was delayed. Discussion: Our detailed characterization of B-cell reconstitution after aHSCT in MS indicates a reduced reactivation potential of memory B cells up to 1 year after transplantation, which may leave patients susceptible to infection, but may also be an important aspect of its mechanism of action.